Primary assessment of water quality and phytoplankton diversity in Dong Rui Wetland, Tien Yen District, Quang Ninh Province - Thuy Nhung, Nguyen; Dương, Thủy Thị; Nguyễn, Đức Anh; Nguyễn, Liên Thùy; Phạm, Dậu Thị (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2SDO - 10.25073/2588-1140/vnunst.4528, 2017)
Primary, Dong Rui was the most pristine mangrove ecosystem in Vietnam with high biodiversity. It services a lot of important ecological functions and values for human. However, it is facing with many problems such as pollution, biodiversity degradation and ecological imbalance. This study was conducted to assess the water quality and phytoplankton diversity of  Dong Rui wetland. The results have recorded 112 algae species, in which Silic algae is dominant in component and density. Physico-chemical parameters and biological indeces showed that the water quality of the Dong Rui area is polluted. Specifically, TSS, PO 4 3- and NH 4 + content exceeded the standard limit of  QCVN10:2015/BTNMT. The H’ index was at 1.33 to 2.92, the C/P index ranged from 0.8 to 5.2, the Dindex was from 0.85 to 2.5. The positive correlation between Margalef and pH, TSS, salinity was found. Interstingly, only C/P index showed the positive and negative relationship with COD and DO, respectively.